Net CO2 assimilation rate response of tomato seedlings (Solanum lycopersicum L.) to the interaction between light intensity, spectrum and ambient CO2 concentration - Moratiel, Rubén; Jimenez, Raúl; Mate, Miriam; Ibánez, Miguel Angel; Moreno, Marta M.; Tarquis, Ana M. (Frontiers in Plant Science, 2023)
Artificial lighting is complementary and single-source lighting for controlled Environment Agriculture (CEA) to increase crop productivity. Installations to control CO2 levels and luminaires with variable spectrum and intensity are becoming increasingly common. In order to see the net assimilation of CO2 based on the relationship between the three factors: intensity, spectrum and CO2 concentration, tests are proposed on tomatoes seedling with combinations of ten spectra (100B, 80B20G, 20B80G, 100G, 80G20R, 20G80R, 100R, 80R20B, 20R80B, 37R36G27B) seven light intensities (30, 90, 200, 350, 500, 700 and 1000 mmol·m-2 s-1) and nine CO2 concentrations (200, 300, 400, 500, 600, 700, 800 and 900 ppm). These tomato seedlings grew under uniform conditions with no treatments applied up to the moment of measurement by a differential gas analyzer. We have developed a model to evaluate and determine under what spectrum and intensity of light photosynthesis the Net assimilation of CO2 (An) is more significant in the leaves of tomato plants, considering the CO2 concentration as an independent variable in the model. The evaluation of the model parameters for each spectrum and intensity shows that the intensity has a more decisive influence on the maximum An rate than the spectra. For intensities lower than 350 mol·m-2 s-1, it is observed that the spectrum has a greater influence on the variable An. The spectra with the best behaviour were 80R20B and 80B20R, which maintained An values between 2 and 4 (mol CO2·m-2·s-1) above the spectra with the worst behaviour (100G, 80G20R, 20G80R and 37B36G27R) in practically all situations. Photosynthetic Light-Use Efficiency (PLUE) was also higher for the 80B20R and 20R80B spectra with values of 36,07 and 33,84 mmol CO2·mol photon-1, respectively, for light intensities of 200 mol·m-2 s-1 and 400 ppm of CO2that increased to values of 49,65 and 48,38 mmol CO2·mol photon-1 for the same light intensity and concentrations of 850 ppm. The choice of spectrum is essential, as indicated by the data from this study, to optimize the photosynthesis of the plant species grown in the plant factory where light intensities are adjusted for greater profitability.